Analisis Prestasi Akademik Mahasiswa Teknik Informatika Institut Teknologi Sumatera (ITERA) Berdasarkan Jalur Seleksi Masuk Perguruan Tinggi Negeri - Mohamad Idris (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2021)
Indicators of student success in the academic at university is the Cumulative grade point average (GPA). Assessed from the Selection Pathways students for State Universities, it is suspected that there are differences in the academic achievement of students. Therefore, this study aims to determine and analyze the academic achievement of students based on the Selection Pathways students at the Department of Informatics Engineering, ITERA. This research is a quantitative research. The population in this study were all students who still active at the Department of Informatics Engineering generation 2017, 2018, and 2019. The samples of this study were 239 (SNMPTN), 239 (SBMPTN), and 35 (Mandiri). The data collection methods were conducted using documentation techniques in the form of GPA data’s students and the Selection Pathways students. Data were analyzed using the ANOVA test. The results of data analysis research were obtained an average GPA of students in the SNMPTN (2.93), SBMPTN (2.89), and Mandiri (2.59). Result of ANOVA test showed that F count (4.363) > F table (3.0133). The conclusion of this study showed that there are significant differences in the academic achievement of students Based on the Selection Pathways for State Universities.